The Effectiveness of Brazil's Environmental Diplomacy in Addressing Amazon Deforestation in the 2019–2023 Period - Qurota Firda Ayuni; Nurbani Adine Gustianti (Perkumpulan Dosen Tarbiyah Islam Indonesia, 2026)
This study aims to determine the effectiveness of Brazil's environmental diplomacy in addressing Amazonian deforestation in the 2019–2023 period. Amazonian deforestation is a global issue closely related to climate change and biodiversity loss. This study uses a qualitative method with a case study approach and a theoretical framework of Institutional Neoliberalism, Two-Level Games, and Environmental Diplomacy. Data were obtained through documentary studies of international organization reports, official government data, and academic literature, with triangulation techniques to increase the validity of the analysis. The results show that Brazil's environmental diplomacy is dynamic and conditional. During the Jair Bolsonaro administration, diplomacy tended to be ineffective due to the mismatch between international commitments and domestic policies that encouraged deforestation. Conversely, during the Luiz Inácio Lula da Silva administration, there was an increase in effectiveness through international institutions and cooperation that resulted in a decrease in deforestation. Thus, the effectiveness of environmental diplomacy is highly dependent on the consistency of domestic policies and the country's institutional capacity.